The Emergence of Antimicrobial Resistance and Virulence Characteristics in Enterococcus Species Isolated from Bovine Milk - Paschoalini, Beatriz Rizzo; Nuñez, Karen Vanessa Munive; Maffei, Juliana Takahashi; Langoni, Hélio [UNESP]; Guimarães, Felipe Freitas [UNESP]; Gebara, Clarice; Freitas, Natylane Eufransino; dos Santos, Marcos Veiga; Fidelis, Carlos Eduardo; Kappes, Roberto; Gonçalves, Mônica Correia; Silva, Nathália Cristina Cirone (MDPI, 2023)
Enterococcus spp., including E. faecalis and E. faecium, pose risks to dairy farms as opportunistic pathogens. The study evaluates antimicrobial resistance (AMR) and virulence characteristics of Enterococcus spp. isolated from bovine milk. Bile esculin agar was used to assess 1471 milk samples, followed by colony identification, gram staining, catalase tests, and 45 °C incubation. PCR analysis targeted E. faecalis and E. faecium in characteristic Enterococcus spp. colonies, with MALDI-TOF used for negative samples. Multiple tests, including disk diffusion, chromogenic VRE agar for vancomycin resistance, Vancomycin Etest® for MIC determination, and PCR for virulence factors (cylA, esp, efaA, ace, asa1, gelE, and hyl genes), were performed. Out of 100 identified strains, E. durans (30.66%), E. faecium (26.28%), and E. faecalis (18.25%) were predominant. AMR in Enterococcus spp. varied, with the highest rates against rifampicin (27%), tetracycline (20%), and erythromycin (18%). Linezolid (5%), vancomycin, ciprofloxacin, and teicoplanin (3% each) had lower prevalence. E. faecium and E. faecalis showed high AMR to rifampicin, erythromycin, and tetracycline. Thirty-two strains (18.98%) grew on VRE Chromoselect agar, while 4 (2 E. faecalis and 2 E. faecium) showed vancomycin resistance by MIC values. E. faecalis carried gelE (45.5%) and asa1 (36%), and E. gallinarum had 9.1% with the asa1 gene. Detecting resistant Enterococcus in bovine milk supports control strategies for enterococci on dairy farms, highlighting AMR concerns in the food chain.
Keywords: E. faecalis; E. faecium; Vancomycin-resistant enterococci (VRE); virulence factors